Mood Disorder in Cancer Patients Undergoing Radiotherapy During the COVID-19 Outbreak - Nardone, Valerio; Reginelli, Alfonso; Vinciguerra, Claudia; Correale, Pierpaolo; Calvanese, Maria Grazia; Falivene, Sara; Sangiovanni, Angelo; Grassi, Roberta; Di Biase, Angela; Polifrone, Maria Angela; Caraglia, Michele; Cappabianca, Salvatore; et al. (Frontiers in Psychology, 2021)
Introduction: Novel coronavirus (COVID-19) is having a devastating psychological impact on patients, especially patients with cancer. This work aims to evaluate mood disorders of cancer patients undergoing radiation therapy during COVID-19 in comparison with cancer patients who underwent radiation therapy in 2019. Materials and Methods: We included all the patients undergoing radiation therapy at our Department in two-time points (each a week for a month in May 2019) and during the COVID-19 outbreak (in April 2020). All the patients were asked to fulfill a validated questionnaire (STAI-Y1, State trait anxiety inventory scale), the Symptom Distress thermometer (SDT) (from 0 to 10 score), and the Beck Depression Inventory v.2 (BDI-2). We took into account the COVID-19 outbreak and also sex, age, week of radiation treatment, and disease. Results: We included 458 patients (220 males and 238 females), with a median age of 64 years. STAI-Y1 median score was 40 (mean 41,3, range 19-79), whereas the median score of SDT was 5 and BDI-2 median score was 11. STAI-Y1, SDT and BDI-2 were significantly correlated with COVID-19 outbreak (p<0,001 for all the tests), sex (p: 0,016 for STAI-Y1, p<0,001 for SDT, p:0,013 for BDI-2), week of treatment (p: 0,012 for STAI-Y1 and p: 0,031 for SDT) and disease (p:0,015 for STAI-Y1, p<0,001 for SDT and p:0,020 for BDI-2). Conclusions: The prevalence of mood disorders in patients undergoing radiation therapy is higher than expected and even higher during the COVID-19 outbreak. These measurements could be useful as a baseline to start medical humanities programs to decrease these scores.